Poop eaters - Lawrence, Ellen, 1967- (Lawrence, Ellen, 1967- Scoop on poop., 2018)
To humans, eating poop sounds disgusting, but many members of the animal kingdom regularly chow down on poop! Filled with information perfectly suited to the abilities and interests of an early elementary audience, this colorful, fact-filled book gives readers a chance not only to learn, but also to develop their powers of observation and critical thinking.